2018
DOI: 10.1257/aer.20160131
|View full text |Cite
|
Sign up to set email alerts
|

The Market for Used Capital: Endogenous Irreversibility and Reallocation over the Business Cycle

Abstract: Capital reallocation is procyclical in the data, but countercyclical in standard businesscycle models. To solve this puzzle, I build a model of endogenous partial irreversibility, with heterogeneous firms facing aggregate and idiosyncratic productivity shocks. Used investment goods are imperfect substitutes for new ones because of firm-level capital specificity. The price of used capital responds to aggregate shocks, leading to equilibrium real-option effects on investment and reallocation. The model generates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Counterfactual simulations revealed that systematic monetary policy exerts stronger effects on real activity in expansions, which implies that monetary policy has to be aggressive in recession to exert the desired stabilizing effect. These results (i) offer support to models featuring “wait‐and‐see” effects (e.g., Bloom, 2009; Bloom et al, 2018; Dibiasi, 2018; Lanteri, 2018) and (ii) justify the rapid and massive monetary policy interventions by the Federal Reserve in response to the COVID‐19 uncertainty shock, which materialized in correspondence of the beginning of a recessionary phase in the USA.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Counterfactual simulations revealed that systematic monetary policy exerts stronger effects on real activity in expansions, which implies that monetary policy has to be aggressive in recession to exert the desired stabilizing effect. These results (i) offer support to models featuring “wait‐and‐see” effects (e.g., Bloom, 2009; Bloom et al, 2018; Dibiasi, 2018; Lanteri, 2018) and (ii) justify the rapid and massive monetary policy interventions by the Federal Reserve in response to the COVID‐19 uncertainty shock, which materialized in correspondence of the beginning of a recessionary phase in the USA.…”
Section: Discussionsupporting
confidence: 63%
“…Our paper, which deals with Bloom's (2009) medium‐scale VAR, shows that Bloom's (2009) results are (i) replicable, (ii) robust to working with nondichotomic uncertainty indicators, and (iii) robust to working with nonlinear frameworks. This result can easily be interpreted in light of the “wait‐and‐see” transmission channel studied by Bloom (2009), Bloom et al (2018), Dibiasi (2018), and Lanteri (2018). Finally, our paper shows that systematic monetary policy is less effective as a stabilization tool during a recession.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…8 Eisfeldt and Rampini (2006) show that trade in used capital, which is part of capital reallocation which they define more broadly, is procyclical and provide a calibrated model with countercyclical reallocation frictions to match this basic fact. Lanteri (2016) shows that the relative price of used capital is procyclical and proposes a model in which new and used capital are imperfect substitutes consistent with this property. 9 Relatedly, Bond (1983) studies trade in used equipment in a model with heterogeneous firms which differ in terms of factor prices and utilization rates.…”
mentioning
confidence: 99%
“…Jovanovic and Rousseau (2002) argue that firms with high book values relative to their costs of capital are simultaneously those most likely to invest and those most likely to engage in acquisitions, suggesting complementarity between the two activities. In addition, Lanteri (2018) shows that the prices of certain capital goods (aircrafts, ships, vehicles, and construction equipment) tend to fall in secondary markets during economic downturns, limiting firms' incentives to sell used capital goods during recessions. Since investment also tends to fall during recessions, this view suggests that underlying macroeconomic shocks would generate a positive relationship between capital reallocation and investment over time.…”
Section: The Link Between Merger and Acquisition Activity And Invementioning
confidence: 99%